In Silico Prediction of Bioactive Peptides from the Simulated Hydrolysis of a Wheat Gluten Protein - Trejo, Diego Arturo Zavala; Arreola, Ariana Rodríguez; Uscanga, Blanca Rosa Aguilar; Pacheco, Josué Raymundo Solís (European Journal of Applied Sciences, 2026)
This study used bioinformatic tools to predict bioactive peptides derived from the high molecular weight DX5 subunit of wheat glutenin. Simulated hydrolysis with pepsin (pH > 2.0) was performed, and the resulting theoretical peptides were evaluated using PeptideRanker and ToxinPred 3.0 to assess bioactivity and toxicity. Among the generated fragments, ten showed a high probability of bioactivity (score ≥ 0.8), and four of them (IF, SF, WQ, and PG) were classified as non-toxic. These findings suggest their potential application in nutraceutical or therapeutic contexts. The in silico approach proves to be an effective and safe strategy for the preliminary identification of functional compounds, providing a foundation for further experimental validation.